(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The general tendency of modern linguistics is oriented towards the comprehensive analysis of language phenomena through the prism of a functional and pragmatic approach. It studies the functions of language units in their interaction with the conditions and tasks of communication. Scientific researches of recent decades are devoted to systematizing general theory principles of communication, the development of the term and methodology definitions, descriptive structures of the communicative act, etc. The main attention of receint researching is focused on describing the strategies and tactics of successful interpersonal and intercultural communication. It is important to investigate factors influencing a communicative act, in particular studying rules, norms and taboos, created to provide successful speaking. Taboo in communication is a kind of protective barrier that prevents moral harm to an interlocutor, and regulates communication behavior. Following prohibitions, along with the principles of courtesy and cooperation, contributes to the successful communication. Analysis of Ukrainian speech practice and fragments of folklore and texts of Ukrainian literature in the end of the XIX – early XXI centuries represents partial verbal and thematic taboos associated with diseases. These partial bans are put on certain categories, as well as discussing the weak condition of a person or his or her health in general. Any disease is concidered to be a living being coming from the other world due to pronuncing by the speaker its name. Such sort of superstition causes the conscious avoidance of these language units in speech. As a result, the words defying human diseases in the speech of Ukrainians become undesirable, and therefore, partially prohibited. This conscious avoidance is connected with the unconventional understanding of a verbal sign and the referential peculiarities of object or reality phenomenon names. It logically brings the formation of numerous word substitutes for the most terrible diseases. Correct decoding of such information messages requires the knowledge of folklore and the symptoms of corresponding illnesses. Also it requires taking into account the context in order to understand the addressee’s thought accurately. In addition communication on the topic of illness is partially forbidden in a certain group of people. However, the current trends in the speech practice of Ukrainians are characterized by the processes of lifting these bans.